Comparison of Downstream Health Care Utilization, Costs, and Long-Term Opioid Use: Physical Therapist Management Versus Opioid Therapy Management After Arthroscopic Hip Surgery. Issue 5 (16th April 2018) - Rhon, Daniel I; Snodgrass, Suzanne J; Cleland, Joshua A; Greenlee, Tina A; Sissel, Charles D; Cook, Chad E
Abstract: Background: Physical therapy and opioid prescriptions are common after hip surgery, but are sometimes delayed or not used. Objective: The objective of this study was to compare downstream health care utilization and opioid use following hip surgery for different patterns of physical therapy and prescription opioids. Design: The design of this study was an observational cohort. Methods: Health care utilization was abstracted from the Military Health System Data Repository for patients who were 18 to 50 years old and were undergoing arthroscopic hip surgery between 2004 and 2013. Patients were grouped into those receiving an isolated treatment (only opioids or only physical therapy) and those receiving both treatments on the basis of timing (opioid first or physical therapy first). Outcomes included overall health care visits and costs, hip-related visits and costs, additional surgeries, and opioid prescriptions. Results: Of 1870 total patients, 82.7% (n = 1546) received physical therapy only, 71.6% (n = 1339) received prescription opioids, and 1073 (56.1%) received both physical therapy and opioids. Because 24 patients received both opioids and physical therapy on the same day, they were eventually removed the final timing-of-care analysis. Adjusted hip–related mean costs were the same in both groups receiving isolated treatments (${\$}$ 11, 628 vs ${\$}$ 11, 579), but the group receiving only physical therapy had significantly lower overall total health care mean costs (${\$}$ 18, 185 vs ${\$}$ 23, 842) and fewer patients requiring another hip surgery. For patients receiving both treatments, mean hip-related downstream costs were significantly higher in the group receiving opioids first than in the group receiving physical therapy first (${\$}$ 18, 806 vs ${\$}$ 16, 955) and resulted in greater opioid use (7.83 vs 4.14 prescriptions), greater total days' supply of opioids (90.17 vs 44.30 days), and a higher percentage of patients with chronic opioid use (69.5% vs 53.2%). Limitations: Claims data were limited by the accuracy of coding, and observational data limit inferences of causality. Conclusions: Physical therapy first was associated with lower hip-related downstream costs and lower opioid use than opioids first; physical therapy instead of opioids was associated with less total downstream health care utilization. These results need to be validated in prospective controlled trials.